Reconnexion de l'Afrique à l'économie mondiale : défis de la mondialisation - Naciri, Abdelali Bensaghi (Codesria book series., 2016)
Achieving a new integration of Africa into the world economy in the neoliberal era prompts discussion of the success and failure of economic policies undertaken so far in African countries; And how to address the factors that currently hamper Africa's development in a globalized economy. What does globalization mean for Africa? What changes does it imply? Which models of development impose, and under what conditions? A comprehension essay is presented in this book.